2020
DOI: 10.1002/ece3.6873
|View full text |Cite
|
Sign up to set email alerts
|

Modeling mycorrhizal fungi dispersal by the mycophagous swamp wallaby (Wallabia bicolor)

Abstract: Animal movement patterns play a role in animal-mediated ecological processes, including propagule dispersal. Mechanisms of propagule dispersal have been widely studied, particularly among plants (Levin et al., 2003). These dispersal mechanisms are diverse and ecologically complex, which makes them challenging to measure or predict; this in turn limits the predictive capacity of dispersal models, almost all of which have been developed for seeds of plants (Aslan et al., 2019). The role of animals in fungal spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…More studies on spore passage rates in many groups of mammals are needed to better understand the processes behind fungal spore dispersal in various mammal species and to develop modelling applications similar to those widely used by plant ecologists. One modelling study showed that swamp wallabies ( Wallabia bicolor ) regularly disperse fungal spores hundreds of metres (in some instances up to 1 265 m) from where the sporocarp was initially ingested ( Danks et al 2020 ). Such long-distance dispersal events have strong ecological significance for fungal taxa, particularly those with sequestrate sporocarp morphologies.…”
Section: Discussionmentioning
confidence: 99%
“…More studies on spore passage rates in many groups of mammals are needed to better understand the processes behind fungal spore dispersal in various mammal species and to develop modelling applications similar to those widely used by plant ecologists. One modelling study showed that swamp wallabies ( Wallabia bicolor ) regularly disperse fungal spores hundreds of metres (in some instances up to 1 265 m) from where the sporocarp was initially ingested ( Danks et al 2020 ). Such long-distance dispersal events have strong ecological significance for fungal taxa, particularly those with sequestrate sporocarp morphologies.…”
Section: Discussionmentioning
confidence: 99%
“…Given that this region has one of the most thoroughly studied communities of small mycophagous mammals (Claridge and May 1994;Nuske et al 2017;Elliott et al 2022), it is possible to test whether the presence of prey mammals known to eat fungi is correlated with the presence of spores in predator faeces. Despite the ecological importance of mycorrhizal fungi, only one previous study has applied modelling to estimate the dispersal potential of a mycophagist (Danks et al 2020). No previous studies have modelled or investigated secondary dispersal by predators.…”
Section: Introductionmentioning
confidence: 99%
“…This may be because research methodology for spore and seed dispersal has not yet been established (Murray, 1988; Otani & Shibata, 2000). Recent developments in molecular biological techniques or global positioning system devices for tracking the movement of life are expected to advance research in this area (Ashley, 2010; Danks et al, 2020; Ma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%